Guide to Computing for Expressive Music Performance - Kirke, Alexis; Miranda, Eduardo R.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Musicians are able to produce an expressive performance of a fixed score by varying the tempo and dynamics of their playing. This is in contrast to computers and sequencers that historically performed tunes in perfect metronomic time, resulting in a (3z(Bmechanic(3y (Bsound. This unique guide/reference presents a broad overview of the work being carried out by the expanding research community dedicated to investigating computer systems for expressive music performance (CSEMPs), covering a significant number of the systems available today. The book discusses all aspects of computing for expressive performance, from the history of CSEMPs to the very latest research, in addition to discussing the fundamental ideas, and key issues and directions for future research. Topics and features: Includes review questions at the end of each chapter Presents a survey of systems for real-time interactive control of automatic expressive music performance, including simulated conducting systems Examines two systems in detail, YQX and IMAP, each providing an example of a very different approach Introduces techniques for synthesizing expressive non-piano performances Addresses the challenges found in polyphonic music expression, from a statistical modelling point of view Discusses the automated analysis of musical structure, and the evaluation of CSEMPs Describes the emerging field of embodied expressive musical performance, devoted to building robots that can expressively perform music with traditional instruments This comprehensive reference is an essential resource for researchers, advanced undergraduates and postgraduates interested in computing for expressive music performance. Music practitioners, music undergraduates, and the general reader will also gain much insight and inspiration from this fascinating text. Prof. Eduardo R. Miranda is a composer and Professor in Computer Music at Plymouth University, UK, where he is Director of the Interdisciplinary Centre for Computer Music Research (ICCMR). Dr. Alexis Kirke is a Research Fellow at ICCMR and composer-in-residency at the Marine Institute - Plymouth University.s
An Overview of Computer Systems for Expressive Music Performance -- Systems for Interactive Control of Computer Generated Music Performance -- Expressive Performance Rendering with Probabilistic Models -- Artificial Evolution of Expressive Performance of Music -- Modelling, Analysing, Identifying and Synthesizing Expressive Popular Music Performances -- Statistical Approach to Automatic Expressive Rendition of Polyphonic Piano Music -- Evaluation of Computer Systems for Expressive Music Performance -- Computational Music Theory and its Applications to Expressive Performance and Composition -- Anthropomorphic Musical Robots Designed to Produce Physically-Embodied Expressive Music Performances.
Keywords: Computer science; Multimedia systems; Artificial intelligence; Computer simulation; Information systems; Music; Computer Science; Computer Appl. in Arts and Humanities; Multimedia Information Systems; User Interfaces and Human Computer Interaction; Artificial Intelligence (incl. Robotics).; Simulation and Modeling; Music